Oral Manifestations of Renal Osteodystrophy in a Patient with Systemic Lupus Erythematosus with Chronic Renal Failure and Secondary Hyperparathyroidism: A Case Report - Riyachan, Inthivorn; Subarnbhesaj, Ajiravudh; Sarideechaigul, Wilairat; Klanrit, Poramaporn (Journal of Dentistry Indonesia, 2019)
Systemic lupus erythematosus (SLE) is one of the chronic autoimmune diseases that leads to multiple manifestations in several organ systems, including chronic renal failure (CRF). Renal osteodystrophy (ROD) is one of the most common complications of CRF associated with secondary hyperparathyroidism (HPT). A combination of CRF and HPT can result in broad-spectrum disorders in the metabolism of minerals such as calcium, phosphorus, and vitamin D, which can affect bone turnover, mineralization, and volume. Radiographic alterations of ROD are considered as one of the earliest signs of CRF. Objective: To describe the oral manifestations in both the maxilla and mandible of a patient with ROD resulting from SLE with CRF and secondary HPT. Case report: A 37-yearold female patient visited the Faculty of Dentistry, Khon Kaen University, for the management of traumatic ulcers on the left and right buccal mucosa and generalized maxillary and mandibular bony hard swellings with mild paresthesia in the lower left mandible for a period of 4 months. The patient had been suffering from SLE for approximately 20 years. However, secondary HPT and CRF as consequences of refractory SLE were being treated concomitantly. Intraoral examination showed several nonpainful ulcers on the left and right buccal mucosa. Radiographic findings revealed generalized loss of lamina dura with thinning of cortical outlines of the maxilla and mandible. Due to complications associated with treatment and the general conditions of this patient, she was referred for treatment to a palliative care unit. Conclusion: Systemic symptoms and complications of patient with ROD with CRF and secondary HPT are seriously problematic. The role of the dentist in this case is to detect the disease, lessen the complications, and make the patient experience minimal pain and side effects in palliative care.